(untitled) (IIUC Studies, 2023)
The Massive Open Online Courses (MOOCs) that aim at developing teachers’ efficiency have been gaining popularity worldwide. Besides enhancing teachers’ knowledge and skills, MOOCs bring a qualitative change in learning and teaching in the educational arena. This qualitative study investigated the difficulties teachers faced in taking MOOCs, the convenience of taking MOOCs by attending camps, and the notable changes in teaching after taking MOOCs. Out of thirty-nine EFL Teachers who in 2018 attended two MOOC camps sponsored by the U.S. Department of State, seventeen participated in this research. The findings reported that teachers’ challenges were primarily technical, technological, procedural, and time constraints. However, taking MOOCs by attending camps was convenient for mutual support, motivation, and best learning practices. The results showed that MOOCs helped teachers raise learners’ intercultural awareness, develop content knowledge, facilitate C.T. skills, and interact more in the EFL classroom. The findings will help policymakers and teacher educators to use MOOCs more effectively for teachers’ continuous professional development. IIUC Studies, Vol.-20, Issue-1, June 2023, pp. 9-32